Impact of corona discharge on Aspergillus niger spores and Cyathus olla mycelium growth - Nedybaliuk, O.A.; Veremii, Yu.P.; Tsvyd, N.V.; Sukhomlyn, M.M.; Tyshchenko, V.G.; Shevchenko, O.V.; Fedirchyk, I.I. (Вопросы атомной науки и техники, 2020)
The article presents an investigation of the influence of the corona discharge with needle-ring electrode configuration on the efficiency of Aspergillus niger spore germination and Cyathus olla mycelium development. Current-voltage characteristics were measured for different distances between the needle and the metal ring. The plot of the dependence of conductance on voltage was built and the corona discharge breakthrough voltage was determined to be (2.7±0.1) kV. The treatment of Aspergillus niger spores was conducted at different development stages: at the germination stage (corona discharge treatment 1 day after the seeding) and dormant state (corona discharge treatment on the day of seeding). The growth rate of Cyathus olla mycelium in samples treated by corona discharge and in control group samples was investigated. The influence of the corona discharge on the potato dextrose agar growth medium before the seeding of Cyathus olla was studied. The pure cultures were obtained from the Culture Collection of Fungi at Kyiv University (FCKU) at the «Institute of Biology and Medicine» Educational and Scientific Centre of the Taras Shevchenko National University of Kyiv. Представлено дослідження впливу коронного розряду з конфігурацією електродів вістря-кільце на ефективність проростання спор Aspergillus niger та розвиток міцелію грибів Cyathus olla. Виміряно вольтамперні характеристики для різних відстаней між вістрям та металевим кільцем. Побудовано графік залежності оберненого опору від напруги, з якого визначено напругу запалювання коронного розряду (2.7±0.1) кВ. Проведено обробку спор Aspergillus niger на різних стадіях розвитку: на стадії проростання (обробка коронним розрядом через добу після висіву) та стадії спокою (обробка коронним розрядом в день висіву). Досліджено швидкість росту міцелію Cyathus olla в зразках, оброблених коронним розрядом, та контрольної групи. Досліджено вплив коронного розряду на картопляно-глюкозний агар до висадження в це середовище Cyathus olla. Чисті культури отримані з Колекції культур грибів FCKU Навчально-наукового центру «Інститут біології та медицини» Київського національного університету ім. Тараса Шевченка. Представлено исследование влияния коронного разряда с конфигурацией электродов острие-кольцо на эффективность прорастания спор Aspergillus niger и развитие мицелия грибов Cyathus olla. Измерены вольтамперные характеристики для различных расстояний между острием и металлическим кольцом. Построен график зависимости обратного сопротивления от напряжения, с которого определено напряжение зажигания коронного разряда (2.7±0.1) кВ. Проведена обработка спор Aspergillus niger на разных стадиях развития: на стадии прорастания (обработка коронным разрядом через сутки после высевания) и стадии покоя (обработка коронным разрядом в день высевания). Исследована скорость роста мицелия Cyathus olla в образцах, обработанных коронным разрядом, и контрольной группы. Исследовано влияние коронного разряда на картофельно-глюкозный агар до высадки в эту среду Cyathus olla. Чистые культуры, получены из коллекции культур грибов FCKU Учебно-научного центра «Институт биологии и медицины» Киевского национального университета им. Тараса Шевченко.